LOCATING PATRIARCHY IN VIOLENCE AGAINST WOMEN IN INDIA: SOCIAL, LEGAL AND ALTERNATIVE RESPONSES - Dutt, Ayurshi (PEOPLE: International Journal of Social Sciences, 2018)
From womb to tomb, women in India are subjected to different forms of violence. Contemporarily, persistent violence against women is leading to its normalization but what lacks is an interrogation of its causes. In this paper, I outline how patriarchy is a promising concept to explain instances of male violence, and how conscious use of violence bolsters the mechanism of subordination. This paper aligns with feminist analyses which evoke gender-power relations, male dominance and female subordination which serve to maintain patriarchy and perpetuate systematic violence against women. Secondly, this paper discusses the legal framework of the criminal justice system in India, asserting that it is not meaningfully reformed, and endures a patriarchal narrative. Women’s courts as alternative approaches which evade formal legal structures are discussed and their empowerment framework is critically analyzed. Furthermore, the public outcry to multiple forms of violence against women is compared to highlight that there are marginalized forms of violence against women, and marginalized women whose experiences of violence have been underrepresented.